'Gay Sex Kits': Lessons in the History of British Sex Education. Issue 1 (2nd January 2021) - Davis, Glyn
Abstract: This article details the genesis, making, release and reaction to 'Homosexuality: A Fact of Life', an educational tape-slide kit produced by the Tyneside branch of the Campaign for Homosexual Equality in the late 1970s. The kit is situated in relation to the history of sex education in Britain and beyond, and compared to other subsequent examples of educational materials that have caused a furore: the book Jenny Lives With Eric and Martin and its connection to Section 28, and the No Outsiders programme that generated protests in 2019. It is argued that the tactics adopted by the makers of 'Homosexuality: A Fact of Life' could serve as a valuable toolbox for future activists.